Zapisz wyrazenia , nie uzywajac nawiasow . Zredukuj wyrazy podobne .
a) x + (3x - y² + 7 )
b) -a + ( 2a - 3b - 1 )
c)- x² + ( x² - x - 7 )
d) -b³ - ( b³ - b² - b )
e) ( 2a - 3b ) + ( 4a - b )
f) - (x² - 3x ) + ( x² + 3x )
g) (a + b - c ) - ( 2a - b + 2c)
h) - ( x² - xy - z ) - ( - x² + 2xy + 2z )

3

Odpowiedzi

2009-11-02T13:25:40+01:00
A) 4x-y²+7
b) a-3b-1
c) -x-7
d) -b²+b
e) 6a-4b
f) 6x
g) -a+2b-3c
h) -3xy+z
13 3 13
Najlepsza Odpowiedź!
2009-11-02T13:27:47+01:00
A) x + (3x - y² + 7 ) = x + 3x - y² + 7 = 4x - y² + 7
b) -a + ( 2a - 3b - 1 ) = -a + 2a - 3b - 1 = a - 3b - 1
c)- x² + ( x² - x - 7 ) = - x² + x² - x - 7 = 2x² - x - 7
d) -b³ - ( b³ - b² - b ) = -b³ - b³ - b² - b = -2b³ - b² - b
e) ( 2a - 3b ) + ( 4a - b ) = 2a - 3b + 4a - b = 6a - 4b
f) - (x² - 3x ) + ( x² + 3x ) = - x² + 3x + x² + 3x = 6x
g) (a + b - c ) - ( 2a - b + 2c) = a + b - c - 2a + b - 2c= -a + 2b - 3c
h) - ( x² - xy - z ) - ( - x² + 2xy + 2z ) = - x² + xy + z + x² - 2xy - 2z = 2x² - z - xy

dasz mi naj?
37 4 37
2009-11-02T13:32:43+01:00
A) x + (3x - y² + 7 )= x + 3x - y² + 7= 4x -y² + 7

b) -a + ( 2a - 3b - 1 )= -a +2a - 3b - 1= a - 3b - 1

c)- x² + ( x² - x - 7 )= - x² + x² - x - 7 = - x - 7

d) -b³ - ( b³ - b² - b )= -b³ - b³ +b² + b= -2b³ +b² + b

e) ( 2a - 3b ) + ( 4a - b )= 2a - 3b + 4a - b = 6a - 4b

f) - (x² - 3x ) + ( x² + 3x )= -x² + 3x + x² + 3x= 6x

g) (a + b - c ) - ( 2a - b + 2c) = a + b - c -2a -b- 2c= a- 3c

h) - ( x² - xy - z ) - ( - x² + 2xy + 2z )= -x² + xy + z - x² - 2xy - 2z= -2x² - xy -z
9 4 9